Effect of Magnetic Field on the Flame Characteristics of Droplet Combustion of Coconut and Palm Oil - Dony Perdana; Asrori Asrori; Muhamad Hanifudin; Novembrian Isam Dinata (The University of Lampung, 2023)
Experimental has been conducted on the effects of variations in the direction of the magnetic fields on flames characteristic of droplets combustion of coconut and palm oils. Two variations of the directions magnetic field N-N and S-N were used in this experiment by placing droplets of vegetable oils on the type K thermocouple between two permanent magnet rods. High-speed camera (120 frame per second) recorded the flames up to extinguished. The result showed that S-N magnetic fields affected on shorter burning time of coconut and palm oil, respectively 670 ms and 871 ms, with the highest temperature of 816.25 oC and 778 oC. The flame height produced by the S-N magnetic field in coconut oil is 34.36 mm shorter, ignitions delay time for all oils has faster than the N-N magnetic field. The strong magnetic field direction increases the oxygen concentrations and fuel molecules around the reaction zone, causing shorter combustion. This combustion produces different flame evolution, shape, height, temperature, and ignition delay times. Keywords: Flames evolution, Flames height, Flames temperature, Ignition delay, Vegetable oils.